The Impact of Donor Risk Index, Recipients’ and Operative Characteristics on Post Liver Transplant One-Year Graft Failure: A Cohort Analysis - Cardoso,Filipe S. (2023)
Abstract Background and Aims: The donor risk index (DRI) quantifies donor-related characteristics potentially associated with increased risk of early graft failure. We aimed to assess the impact of the DRI, recipient and perioperative factors on post liver transplant (LT) outcomes. Methods: This was a single-center retrospective cohort study including all adult (≥18 years) patients who underwent LT from 01/2019 to 12/2019 at Curry Cabral Hospital, Lisbon, Portugal. Primary endpoint was 1-year graft failure post LT. Associations were studied with logistic regression. Results: A total of 131 cadaveric donor LT procedures were performed in 116 recipients. Recipients’ median (IQR) age was 57 (47-64) years and 101/131 (77.1%) were males. Cirrhosis was the underlying etiology in 95/131 (81.2%) transplants. Based on 8 predefined donors’ characteristics, median (IQR) DRI was 1.96 (1.67-2.16). Following adjustment for MELDNa score pre LT and SOFA score (adjusted odds ratio [aOR], 95% confidence interval [CI] =0.91 [0.56-1.47]) or lactate (aOR [95% CI] = 2.76 [0.71-10.7]) upon intensive care unit (ICU) admission post LT, DRI was not associated with 1-year graft failure. However, higher SOFA score (aOR [95% CI] = 1.20 [1.05-1.37]) or lactate (aOR [95% CI] = 1.27 [1.10-1.46]) upon ICU admission post LT were independently associated with higher odds of 1-year graft failure. Conclusions: In a recent cohort of patients who under-went LT, DRI, despite being high, was not associated with 1-year graft failure, but SOFA score or lactate upon ICU ad-mission post LT were.